Empowering Women and Youth through Entrepreneurship and MSME Training Based on Digital Marketing in Rural Communities - Anisyah, Andini Nur; Fransisca, Cindy; Nabillah, Haura; Pohan, Nurul Yesila; Dewi, Ika Sandra (Raskha Media Group, 2025)
Rural communities often face limited access to digital skills and entrepreneurial resources, particularly among women and youth. This community engagement program was designed to strengthen their capacity to manage micro and small enterprises through applied digital marketing training. The activities combined socialization sessions, practical workshops, and mentoring programs conducted in Empat Negeri Village, Batu Bara Regency, involving 30 local participants. The training covered topics such as creating digital business profiles, developing promotional content, and managing sales through online platforms. Evaluation was carried out using observation, pre- and post-assessment, and qualitative interviews to measure knowledge, skill, and confidence growth. The results showed an average increase of 40–55% in participants’ understanding of online marketing strategies, digital content creation, and customer engagement techniques. In addition, several participants successfully expanded their market reach through social media. Beyond technical gains, the activities fostered collaboration among women and youth, encouraging innovation and economic independence within the community. Keywords: community empowerment; digital marketing; entrepreneurship training; MSMEs; women and youth